Glycerol dehydration catalyzed by MWW zeolites and the changes in the catalyst deactivation caused by porosity modification - Rodrigues, Mariana Veiga [UNESP]; Vignatti, Charito; Garetto, Teresita; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Martins, Leandro [UNESP] (Elsevier B.V., 2015)
Members of the layered MWW family, including microporous MCM-22, pillared MCM-36 and delaminated ITQ-2 zeolites, were used as catalysts for the gas phase dehydration of glycerol. The chemical, structural and surface properties of the catalysts were characterized by X-ray diffraction, N-2 adsorption-desorption isotherms, SEM, TEM, NH3-TPD and pyridine chemisorption followed by IR spectroscopy. The results clearly showed that the modified zeolites with designed mesopore structure enabled rapid diffusion and consequently improved the glycerol conversion. Characterization of the acid sites revealed that the relative abundance of Bronsted and Lewis acid sites influenced the efficiency of the catalysis performed by these materials. C-13 NMR spectra of the spent catalysts confirmed that differences in the nature and amount of carbonaceous deposits are related to the pore structures of the catalysts, with greater formation of polyaromatic compounds inside zeolite pores, while polyglycols are preferentially formed at the external surfaces of the MCM-36 and ITQ-2 zeolites, as expected for the more exposed sheets.
Keywords: MWW zeolites; Glycerol dehydration; Deactivation; Pillarization; Delamination